ANALISIS PERTUMBUHAN KAWASAN PENGEMBANGAN EKONOMI TERPADU (KAPET) BIAK DI PROVINSI PAPUA - Johanis M Siren (TATALOKA, 2016)
The purpose of this study was to analyze the regional typology, the leading sectors and the potential of fish resources in Biak Kapet (Integrated Economic Development Zone). The tools of analysis used were Klassen Typology, LQ/SSA/Overlay methods and Maximum Sustainable Yield (MSY). Results of this study show that Biak Kapet can be classified as a less developed region on the aspect of economic growth and income per capita. However, with regard to human development index (HDI) and economic growth, it occurs to be fast growing except Waropen Regency (Kabupaten). Waropen and Supiori Regencies have agriculture, industry, construction, and services as the leading sectors while Nabire, Yapen and Biak Numfor Islands have competitive and comparative sectors. Regional development of the Kapet should be based on the local potential of each subregion. So, every regency in the Kapet should develop its local potential supported by the land carrying capacity. The highest level of land carrying capacity for agriculture sector is in Nabire Regency, and the lowest is in Supiori. In addition to resources that have been being utilized by every regency in Biak Kapet, there are also common pool resources (CPRs) not yet developed integratively. It is the sea, which has the potential of fish resources although with fluctuating levels of maximum sustainable yield. Nevertheless, the potential can be relied upon to improve economic growth and income per capita of every subregion in Biak Kapet.